Rural poverty and inequality in Ethiopia: does access to small-scale irrigation make a difference? - Namara, Regassa E.; Makombe, Godswill; Hagos, Fitsum; Awulachew, Seleshi Bekele (2010)
The underlying causes of rural poverty are many in Ethiopia, however, the persistent fluctuation in the amount and distribution of rainfall is considered as a major contributing factor. Cognizant of this reality the successive Ethiopian governments, NGOs and farmers have made considerable investments in small-scale irrigation systems. This paper analyzes the efficacy of these investments in reducing poverty based on data obtained from a survey of 1024 farmers drawn from four major regional states of Ethiopia. The Foster, Greer and Thorbecke poverty indices were used to compare the incidence, depth and severity of poverty among groups of farmers defined by relevant policy variables including access to irrigation. Logistic regression model was fitted to explore the correlates of rural poverty. The main conclusion of the study is that poverty is affected more by the intensity of irrigation use than mere access to irrigation and there seem to be an economy of scale in the poverty-irrigation nexus.